2015
DOI: 10.1002/bdm.1906
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Scientific Reasoning Scale

Abstract: Scientific findings and innovations play an important role in a range of decisions faced by nonscientists, yet little is known about the skills that nonscientists need in order to read and evaluate scientific evidence. Drawing on research in public understanding of science, cognitive developmental psychology, and behavioral decision research, we develop an individual difference measure of scientific reasoning skills, defined as the skills needed to evaluate scientific findings in terms of the factors that dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(167 citation statements)
references
References 35 publications
5
151
3
4
Order By: Relevance
“…The SRS is an 11-item test that presents subjects with a scientific scenario and asks them a true/false question related to the scenario (Drummond & Fischhoff, 2017a). The SRS is constructed to test understanding of general scientific concepts, such as random assignment, causal inference, ecological validity, and so on.…”
Section: Scientific Reasoning Scalementioning
confidence: 99%
“…The SRS is an 11-item test that presents subjects with a scientific scenario and asks them a true/false question related to the scenario (Drummond & Fischhoff, 2017a). The SRS is constructed to test understanding of general scientific concepts, such as random assignment, causal inference, ecological validity, and so on.…”
Section: Scientific Reasoning Scalementioning
confidence: 99%
“…Our study included both a measure of subjective knowledge about each biotechnology product and objective ability to think scientifically. Ability to think scientifically, rather than testing for fact-based knowledge, tests for general scientific reasoning skills [4]. Interestingly, we found that individuals who perceived biotechnology to be risky and believed it needed to be regulated had strong scientific reasoning skills, a subtle-yet important-distinction from previous findings.…”
Section: Discussionmentioning
(Expert classified)
“…The survey established basic demographics about respondents including age, gender, ethnicity, level of education, political ideology, and income. Previously established groups of questions were included to measure pro-environmentalism (New Environmental Paradigm: NEP) [15], personal values [16], and scientific reasoning skills [4]. In addition to these established scales, questions based on the willingness to sacrifice framework [17], about levels of trust in academic, government, and industry scientists, and about religious beliefs were also used to generate scales.…”
Section: Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also comparable with other sources like. 47 The use of the factor analysis for the determination of construct validity, showed acceptable results, the items of research tool were distributed into three factors and all conditions for the use of the exploratory factor analysis were respected. During the use of the factor analysis, it was accepted that one item in one factor and every factor loading score for the item was higher than 0.40.…”
Section: Resultsmentioning
confidence: 99%